Comparison of selected kinematic variables front- and rear- weighted track start of elite male swimmers - Mohamad-fazel Sabaghi; Masoud Mirmoezzi; Parasto Mohamadian (Biyumikānīk-i varzishī, 2018)
Objective: Over recent years, due to scientific advances in various aspects of sport, rapid development and improvement has taken place in sport performance standards as well as athletes' performance. In the swimming tournament starting on time and correctly, one of the factors that plays an important role in the success of swimmers, especially speed swimmers. The aim of this study was Comparison of selected kinematic variables frontand rear- weighted track start of elite male swimmers. Methods: Fourteen male elite male swimmers with an average age of 17.86±1.92 years were targeted and available among those who had better starters and had the right foot (dominant legs) place in this study. The following kinematic parameters were analysed: take off angle, take off velocity, entry angle, entry velocity and flight distance. Used a top speed of 100 fps video camera to detect body position and biomechanical parameters during the performance two start techniques.the statistical methods were Kolmogorov-smirnov test to chek for normal distribution of data and T-test for comparison between two types of kinematic quantities start with 0.05 alpha levels. Results: Findings indicated that flight distance were significant difference between two start techniques (P<0.05) and the distance at Frontand- weighted track start was more than the distance at rear- weighted track start. Conclusion: Because of the difference in flight distance and Time off the platform in two types of startes, coaches and swimmers can use either of the two startes depending on the type of competition (Speed and endurance of swimming).